Shoot Girdling Improves Rooting Performance of Kalamata Olive Cuttings by Upregulating Carbohydrates, Polyamines and Phenolic Compounds - Nikoleta-Kleio Denaxa; Stavros N. Vemmos; Peter A. Roussos (Agriculture, 2021)
Girdling (a ring of bark approximately 5 mm wide) was applied on olive mother plants to investigate its effect on the rooting ability of cuttings. Treatment was applied in autumn and in spring. The cuttings were then immersed for 5 s into 2000 mg L−1 indole-3-butyric acid (IBA) in a 45% v/v ethanolic solution. Thirty days after girdling, cuttings were taken from girdled and control shoots from the part just above the girdle zone (basal), as well as from the part right above (middle). The base of the cuttings was collected, and the concentration of polyamines, phenolic compounds and soluble carbohydrates was determined. Girdling enhanced the rooting performance of the cuttings, while autumn proved to be a better season for rooting compared to spring. Girdling positively affected the concentration of all the measured parameters. The main characteristics of autumn cuttings were the high levels of glucose, mannitol, free and total polyamines, hydroxytyrosol, tyrosol, verbascoside, oleuropein, quercetin and luteolin. The cuttings taken from the middle part of the girdled shoot exhibited high sucrose, glucose, mannitol, free polyamines, hydroxytyrosol, luteolin-7-glucoside, total phenols and flavanol concentrations. Nonetheless, further research is needed in order to draw conclusions on the overall efficiency of girdling on inducing rooting of olive cuttings.